The sides $a,b,c$ of $\vartriangle ABC$, are in A.P. If $\cos \alpha = \dfrac{a}{{b + c}}$, $\cos \beta = \dfrac{b}{{c + a}}$, $\cos \gamma = \dfrac{c}{{a + b}}$ then ${\tan ^2}\dfrac{\alpha }{2} + {\tan ^2}\dfrac{\gamma }{2} = $
A.1
B.$\dfrac{1}{2}$
C.$\dfrac{1}{3}$
D.$\dfrac{2}{3}$
Answer
Verified
483k+ views
Hint: Since, the sides of the triangle are in A.P, let $d$ be the common difference of A.P and rewrite the sides as $a = b - d$, $b$ and $c = b + d$. Then, substitute the values in the given equation $\cos \alpha = \dfrac{a}{{b + c}}$, $\cos \beta = \dfrac{b}{{c + a}}$, $\cos \gamma = \dfrac{c}{{a + b}}$ and simplify using the trigonometric formulas. Further, find the value of ${\tan ^2}\dfrac{\alpha }{2} + {\tan ^2}\dfrac{\gamma }{2}$.
Complete step-by-step answer:
We are given that the sides of a triangle are in A.P
Let $d$ be the common difference of A.P
Then, the sides of A.P. can be written as $a = b - d$, $b$ and $c = b + d$
Also, we are given than $\cos \alpha = \dfrac{a}{{b + c}}$
Substitute the value of $a,b,c$ in the equation.
$\cos \alpha = \dfrac{{b - d}}{{b + b + d}}$
$ \Rightarrow \cos \alpha = \dfrac{{b - d}}{{2b + d}}$ (1)
Similarly, we will write the value of $\cos \beta = \dfrac{b}{{c + a}}$
Hence, we get,
$
\cos \beta = \dfrac{b}{{b + d + b - d}} \\
\Rightarrow \cos \beta = \dfrac{b}{{2b}} \\
\Rightarrow \cos \beta = \dfrac{1}{2} \\
\Rightarrow \beta = {60^ \circ } \\
$
Now, we will write the value of $\cos \gamma = \dfrac{c}{{a + b}}$
$
\cos \gamma = \dfrac{c}{{a + b}} \\
\Rightarrow \cos \gamma = \dfrac{{b + d}}{{b - d + b}} \\
$
$ \Rightarrow \cos \gamma = \dfrac{{b + d}}{{2b - d}}$ (2)
Now, we know that $\cos \left( {2x} \right) = \dfrac{{1 - {{\tan }^2}x}}{{1 + {{\tan }^2}x}}$
Therefore from equation (1), we have,
$
\cos \alpha = \dfrac{{1 - {{\tan }^2}\dfrac{\alpha }{2}}}{{1 + {{\tan }^2}\dfrac{\alpha }{2}}} \\
\Rightarrow \dfrac{{b - d}}{{2b + d}} = \dfrac{{1 - {{\tan }^2}\dfrac{\alpha }{2}}}{{1 + {{\tan }^2}\dfrac{\alpha }{2}}} \\
$
We will solve the above equation to find the value of ${\tan ^2}\dfrac{\alpha }{2}$
Use componendo and dividendo rules to simplify the equation.
$
\dfrac{{b - d - 2b - d}}{{b - d + 2b + d}} = \dfrac{{1 - {{\tan }^2}\dfrac{\alpha }{2} - 1 - {{\tan }^2}\dfrac{\alpha }{2}}}{{1 - {{\tan }^2}\dfrac{\alpha }{2} + 1 + {{\tan }^2}\dfrac{\alpha }{2}}} \\
\Rightarrow \dfrac{{ - b - 2d}}{{3b}} = \dfrac{{ - 2{{\tan }^2}\dfrac{\alpha }{2}}}{2} \\
\Rightarrow {\tan ^2}\dfrac{\alpha }{2} = \dfrac{{2d + b}}{{3b}} \\
$
Similarly, we will find the value of ${\tan ^2}\dfrac{\gamma }{2}$ from equation (2)
$
\Rightarrow \cos \gamma = \dfrac{{1 - {{\tan }^2}\dfrac{\gamma }{2}}}{{1 + {{\tan }^2}\dfrac{\alpha }{2}}} \\
\Rightarrow \dfrac{{b + d}}{{2b - d}} = \dfrac{{1 - {{\tan }^2}\dfrac{\gamma }{2}}}{{1 + {{\tan }^2}\dfrac{\gamma }{2}}} \\
$
Use componendo and dividendo rules to simplify the equation.
$
\dfrac{{b + d - 2b + d}}{{b + d + 2b - d}} = \dfrac{{1 - {{\tan }^2}\dfrac{\gamma }{2} - 1 - {{\tan }^2}\dfrac{\gamma }{2}}}{{1 - {{\tan }^2}\dfrac{\gamma }{2} + 1 + {{\tan }^2}\dfrac{\gamma }{2}}} \\
\Rightarrow \dfrac{{ - b + 2d}}{{3b}} = \dfrac{{ - 2{{\tan }^2}\dfrac{\gamma }{2}}}{2} \\
\Rightarrow {\tan ^2}\dfrac{\gamma }{2} = \dfrac{{b - 2d}}{{3b}} \\
$
We will now substitute the values of ${\tan ^2}\dfrac{\alpha }{2}$ and ${\tan ^2}\dfrac{\gamma }{2}$ in the expression ${\tan ^2}\dfrac{\alpha }{2} + {\tan ^2}\dfrac{\gamma }{2}$
$
\dfrac{{2d + b}}{{3b}} + \dfrac{{b - 2d}}{{3b}} = \dfrac{{2d + b + b - 2d}}{{3b}} \\
\Rightarrow \dfrac{{2b}}{{3b}} \\
\Rightarrow \dfrac{2}{3} \\
$
Hence, the value of ${\tan ^2}\dfrac{\alpha }{2} + {\tan ^2}\dfrac{\gamma }{2}$ is $\dfrac{2}{3}$.
Thus, option D is correct.
Note: Here, we have used the formula of $\cos \left( {2x} \right) = \dfrac{{1 - {{\tan }^2}x}}{{1 + {{\tan }^2}x}}$, where the angle gets half. Similarly, we have $\cos \left( {2x} \right) = {\cos ^2}x - {\sin ^2}x$, $\cos \left( {2x} \right) = 1 - 2{\sin ^2}x$ and $\cos \left( {2x} \right) = 2{\cos ^2}x - 1$. Use the formula according to the condition in the question.
Complete step-by-step answer:
We are given that the sides of a triangle are in A.P
Let $d$ be the common difference of A.P
Then, the sides of A.P. can be written as $a = b - d$, $b$ and $c = b + d$
Also, we are given than $\cos \alpha = \dfrac{a}{{b + c}}$
Substitute the value of $a,b,c$ in the equation.
$\cos \alpha = \dfrac{{b - d}}{{b + b + d}}$
$ \Rightarrow \cos \alpha = \dfrac{{b - d}}{{2b + d}}$ (1)
Similarly, we will write the value of $\cos \beta = \dfrac{b}{{c + a}}$
Hence, we get,
$
\cos \beta = \dfrac{b}{{b + d + b - d}} \\
\Rightarrow \cos \beta = \dfrac{b}{{2b}} \\
\Rightarrow \cos \beta = \dfrac{1}{2} \\
\Rightarrow \beta = {60^ \circ } \\
$
Now, we will write the value of $\cos \gamma = \dfrac{c}{{a + b}}$
$
\cos \gamma = \dfrac{c}{{a + b}} \\
\Rightarrow \cos \gamma = \dfrac{{b + d}}{{b - d + b}} \\
$
$ \Rightarrow \cos \gamma = \dfrac{{b + d}}{{2b - d}}$ (2)
Now, we know that $\cos \left( {2x} \right) = \dfrac{{1 - {{\tan }^2}x}}{{1 + {{\tan }^2}x}}$
Therefore from equation (1), we have,
$
\cos \alpha = \dfrac{{1 - {{\tan }^2}\dfrac{\alpha }{2}}}{{1 + {{\tan }^2}\dfrac{\alpha }{2}}} \\
\Rightarrow \dfrac{{b - d}}{{2b + d}} = \dfrac{{1 - {{\tan }^2}\dfrac{\alpha }{2}}}{{1 + {{\tan }^2}\dfrac{\alpha }{2}}} \\
$
We will solve the above equation to find the value of ${\tan ^2}\dfrac{\alpha }{2}$
Use componendo and dividendo rules to simplify the equation.
$
\dfrac{{b - d - 2b - d}}{{b - d + 2b + d}} = \dfrac{{1 - {{\tan }^2}\dfrac{\alpha }{2} - 1 - {{\tan }^2}\dfrac{\alpha }{2}}}{{1 - {{\tan }^2}\dfrac{\alpha }{2} + 1 + {{\tan }^2}\dfrac{\alpha }{2}}} \\
\Rightarrow \dfrac{{ - b - 2d}}{{3b}} = \dfrac{{ - 2{{\tan }^2}\dfrac{\alpha }{2}}}{2} \\
\Rightarrow {\tan ^2}\dfrac{\alpha }{2} = \dfrac{{2d + b}}{{3b}} \\
$
Similarly, we will find the value of ${\tan ^2}\dfrac{\gamma }{2}$ from equation (2)
$
\Rightarrow \cos \gamma = \dfrac{{1 - {{\tan }^2}\dfrac{\gamma }{2}}}{{1 + {{\tan }^2}\dfrac{\alpha }{2}}} \\
\Rightarrow \dfrac{{b + d}}{{2b - d}} = \dfrac{{1 - {{\tan }^2}\dfrac{\gamma }{2}}}{{1 + {{\tan }^2}\dfrac{\gamma }{2}}} \\
$
Use componendo and dividendo rules to simplify the equation.
$
\dfrac{{b + d - 2b + d}}{{b + d + 2b - d}} = \dfrac{{1 - {{\tan }^2}\dfrac{\gamma }{2} - 1 - {{\tan }^2}\dfrac{\gamma }{2}}}{{1 - {{\tan }^2}\dfrac{\gamma }{2} + 1 + {{\tan }^2}\dfrac{\gamma }{2}}} \\
\Rightarrow \dfrac{{ - b + 2d}}{{3b}} = \dfrac{{ - 2{{\tan }^2}\dfrac{\gamma }{2}}}{2} \\
\Rightarrow {\tan ^2}\dfrac{\gamma }{2} = \dfrac{{b - 2d}}{{3b}} \\
$
We will now substitute the values of ${\tan ^2}\dfrac{\alpha }{2}$ and ${\tan ^2}\dfrac{\gamma }{2}$ in the expression ${\tan ^2}\dfrac{\alpha }{2} + {\tan ^2}\dfrac{\gamma }{2}$
$
\dfrac{{2d + b}}{{3b}} + \dfrac{{b - 2d}}{{3b}} = \dfrac{{2d + b + b - 2d}}{{3b}} \\
\Rightarrow \dfrac{{2b}}{{3b}} \\
\Rightarrow \dfrac{2}{3} \\
$
Hence, the value of ${\tan ^2}\dfrac{\alpha }{2} + {\tan ^2}\dfrac{\gamma }{2}$ is $\dfrac{2}{3}$.
Thus, option D is correct.
Note: Here, we have used the formula of $\cos \left( {2x} \right) = \dfrac{{1 - {{\tan }^2}x}}{{1 + {{\tan }^2}x}}$, where the angle gets half. Similarly, we have $\cos \left( {2x} \right) = {\cos ^2}x - {\sin ^2}x$, $\cos \left( {2x} \right) = 1 - 2{\sin ^2}x$ and $\cos \left( {2x} \right) = 2{\cos ^2}x - 1$. Use the formula according to the condition in the question.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE